Understanding the democracy of Božidar S. Marković - Kovačević, Slaviša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Overcoming the obvious democracy crisis is possible to be done by taking an insight into our democratic thought. This paper reminds, directs, actualises, values and reminds scientifically-democratic thought of Bozidar S. Markovic, in a real context of strenuous processes of intoducing and consolidating democracy in Serbia. Understanding democracy of Bozidar S. Markovic is a theoretical framework which satisfies criteria of scientific generalisation, for it includes characteristic and essential landmarks of democracy and criteria of methodological contextuality for different and specific experiences of certain countries and their people. In this paper the frameworks of democracy are being thematized, with its characteristics, good and bad sides in the circumstances of our current political practice.Key words: democracy, freedom, equality, democracy advantages, democracy disadvantages
Keywords: Key words: democracy, freedom, equality, democracy advantages, democracy disadvantages